Attention deficit in children in the digital era: A cross-sectional study on the influence of parenting styles and screen exposure - Satya Nagisetty; Sphurti Pusukuri; Mamatha Bellamkonda; M. Vishnu Vardhan; Rajendrakumar Katte (Telangana Journal of Psychiatry)
Background: In this digital era, children are exposed to screens instead of outdoor activities. This has raised concerns about its impact on attention spans and behavioral health. There is also an increase in nuclear families in which both the parents are working. Therefore, the time spent by the parents with their children has significantly reduced. This has also influenced the increase in digital screen usage due to the inevitable boredom of the children. Aims and Objectives: The aim of the study was to study the association of parenting styles, screen usage, and attention deficit in children. Methodology: The study was done on 60 children using a questionnaire of demographic details, modified Kuppuswamy socioeconomic scale 2024, Vanderbilt Attention-Deficit/Hyperactivity Disorder Diagnostic Rating Scale – Parent Informant, Parenting Style Questionnaire for Children and Adolescents and SCREENS – Q which was distributed using a Google form link on social media platforms. Results: The study revealed that the authoritative parenting style was exhibited by most parents. A strong positive correlation was observed between attention deficit and screen exposure followed by a weak correlation between parenting style and screen exposure. This shows that parenting style does not significantly influence screen exposure, indicating that it may not affect the amount of screen time children receive. However, greater screen time is associated with more pronounced attention deficit issues in children. Conclusion: Parenting style has a significant positive relationship with attention deficit. Conversely, parenting style does not appear to significantly influence screen exposure which is instead strongly correlated with attention deficit.